Pengembangan Media Pembelajaran Berbasis Multimedia Pada Subtema Keberagaman Budaya Bangsaku Di Kelas IV Untuk Sekolah Dasar - Kustiana, Tiara Indra; , Drs.Muhroji, SE. M.Si, M.Pd (2017)
This research has something as a purpose for developing media lesson bases multimedia which suitable to be used in sub topic keberagaman budaya bangsaku in grade IV elementary school. The kinds of this research is researching and developing or which was usually called R&D (Research and Development) the stage of researching include collecting data, planning product, improving product, validation by expert media and expert material, trying product and revision product. The First trying product was bought in January 〖30〗^th 2017 by expert material and expert media to get suggestion as taking care revision media product. The second trying product was bought in February 〖13〗^th until 〖18〗^th2017 in field by the students of grade IV elementary school. Rafter trying field was bougt FGD (Focus Group Discission) in March 8^thto 〖10〗^th2017 by expert material, expert media, observer, and the researcher. Media that was developer in this Research is multimedia with joined preture media, sound, video, and animation in the form power point. media which has the shape of picture is performed in the form power point that is given animation be active. Material that is given to practice is performed in video and media that is given writting is added effect sound in order to be cleary.